Military Pain Medicine: Sustaining the Fighting Force. Issue 3 (6th October 2021) - Hughey, Scott; Spevak, Christopher; Stedje-Larsen, Eric
ABSTRACT: Active duty military service members (ADSMs) suffer disproportionately from chronic pain. In the USA, military pain physicians serve an important role in the treatment of pain conditions in addition to the maintenance of the fighting force. Expanding roles for pain physicians, including novel therapies, consulting roles for opioid policy, and usefulness in a deployed setting create enormous value for military pain physicians. Ongoing force structure changes, including proposed reduction in the U.S. Military's healthcare workforce may significantly impact pain care and the health of the fighting forces. Military pain physicians support a variety of different roles in the military healthcare system. Ultimately, maintaining a robust faculty of pain physicians allows for both preservation of the fighting forces and a ready medical force.